Reproductive and productive efficiencies of Etawah Grade goats under various mating managements - Bambang Sunadi; I-K Sutama; I-G.M Budiarsana (Jurnal Ilmu Ternak dan Veteriner, 1998)
Thirty six Etawah Grade (PE) goats were treated with three type of mating managements, i.e. mated at the first oestrous (A), mated at the second oestrous (B), and mated at the third oestrous (C) after parturition, respectively . Results showed that average first estrous was 56 days (26-99 d) after parturition with estrous cycle of 21 days . Conception rate at the first and second oestrous mating managements (A and B) were 50 and 70%, respectively . Variability of birth weight (3,4 - 3,5 kg) under three mating managements were not significantly different (P>0 .05), but the weaning weight of kids of B (16 .4 kg) was higher (P<0.05) than A (11 .8 kg) and C (12.9 kg), respectively. Does productivity (total weaning weight) was not significantly affected by mating management, i.e. at fisrt, second or third oestrous after parturition .   Keywords : Goats, mating management, productivity